Establishment of Regular Postal Service in the Cameroons under British and French Mandates (Colonial Letters and the Contact of Knowledges, 1936)
This file contains colonial letters on the establishment of regular postal service in the Cameroons under British and French mandates
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies